(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare the data of patients who underwent gastric cancer surgery as laparoscopically completed and converted to open surgery and draw attention to complications arising from trocar entry. Materials and Methods: This study included 211 patients who underwent laparoscopic gastric cancer surgery. Patients were divided in to two groups as laparoscopically completed and converted to open surgery. Demographics parameters and perioperative data were retrospectively analyzed. Results: The median age of the study group was 62 (19-91) years and 68.2% were males. Conversion occured in 16 patients (7.5%). The reasons for conversion were locally advanced tumor (n=6), complications due to trocar insertion (n=4), technical difficulty in performing esophagojejunostomy anastomosis (n=4), leakage in esophagojejunostomy anastomosis (n=1), and persistent bradycardia (n=1). Intraoperative blood loss was higher and time to oral intake was longer in the conversion group. No significant difference was found in terms of demographic parameters, operative time, length of hospital stays, the rate of postoperative complications, reoperation, 30-day mortality. Conclusion: Complications due to trocar entry is an unpredictable and preventable conversion reason in laparoscopic gastric cancer surgery. Thin patients are riskier for complications during abdominal access. Abdominal access should be performed with an open technique in thin patients